2021
DOI: 10.1177/07356331211051023
|View full text |Cite
|
Sign up to set email alerts
|

Individual Experience and Engagement in Avatar-Mediated Environments: The Mediating Effect of Interpersonal Attraction

Abstract: The application of different virtual reality interventions has been recently gaining interest from researchers and practitioners. Due to the current COVID-19 pandemic, higher education institutions increased the use of these technologies to help create much value for educators and students. The relationship between individual experience and engagement in avatar-mediated environments has garnered empirical support, but still little is known about the mediating mechanisms underlying this relation. This study inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Laurens-Arredondo [130] also presents a pilot study showing the positive impact of mobile learning and AR on motivation and meaningful learning in Engineering-related programs. One last publication reported using XR to find a nexus between an individual's positive experience and online engagement in avatar-mediated environments in students enrolled in a design course [131].…”
Section: Behavioral and Psychological Impactmentioning
confidence: 99%
“…Laurens-Arredondo [130] also presents a pilot study showing the positive impact of mobile learning and AR on motivation and meaningful learning in Engineering-related programs. One last publication reported using XR to find a nexus between an individual's positive experience and online engagement in avatar-mediated environments in students enrolled in a design course [131].…”
Section: Behavioral and Psychological Impactmentioning
confidence: 99%
“…The teachers are using AR and VR as innovative educational tools for a better teaching-learning experience. Teachers reported that using these technologies has increased student engagement, interaction, cognitive skills and social skills (Alblehai, F.M., 2022; Lamo et al ., 2022; Zholaushievna et al ., 2022). Moreover, students also reported high retention and better learning experience when using AR and VR (Baabdullah et al ., 2022; Nounou et al ., 2022; Monfared et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%